Prevalence of Adverse Drug Reactions of Anti-Hypertensive Drugs in A Tertiary Care Hospital, Bhairahawa, Nepal - Palikhey, Anjan; Chaudhary, Ramita; Shrestha , Laxmi; Shrivastava , Amit Kumar; Kumar Yadav, Chandrajeet; Giri, Anish; Kumar Sah, Ajit; Shrestha , Jharana (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Hypertension represents the common disease worldwide which mostly requires long-term therapy and combination of two or more antihypertensive drugs. These drugs are frequently linked to adverse drug reactions. The objective of the study was to determine the prevalence of adverse drug reactions in patients under anti-hypertensive drugs. Methods The study was a cross-sectional study conducted among 250 hypertensive patients under medications at the medicine department of Universal College of Medical Sciences- Teaching Hospital. Face-to-face interviews were used to gather the data, which was then recorded on an adverse medication reaction monitoring form. Naranjo algorithm scale was used to categorize the causality relationship of adverse drug reactions. Results Out of 250 hypertensive patients, a total of 73 ADR cases (29.2%) were observed. The most commonly linked drugs with ADRs were calcium channel blockers (65.8%) followed by ARBs (12.3%), Beta-blockers (9.6%) and Diuretics (6.8%). Amlodipine (62.9%) was found to be the most frequently linked drug to ADR. Most of the ADRs in the current study fell under category possible (38.3%) followed by definite (28.8%), probable (21.9%) and doubtful (11%) respectively. Conclusions Patients taking anti-hypertensive drugs commonly experience adverse drug reactions. The study recommends that ADR monitoring be conducted continually in hospital settings in order to identify and document any adverse effects brought on by various drugs so that it would be helpful for doctors to rationally prescribe.